2013
DOI: 10.1520/jte20120134
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage and Creep of Steel Fiber Reinforced Normal Strength Concrete

Abstract: This paper deals with the results of laboratory research into the time-related development of shrinkage and creep in normal strength concrete that has been steel fiber reinforced with volumetric contents of up to 2.0 % of shorter (l = 16 mm) or longer (l = 30 mm) steel fibers. The experimental research refers to the respective effects of the length and volumetric content of such fibers, as well as to the effect of early water curing conditions on the shrinkage and creep of the composite concerned. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Some researchers found that the shrinkage properties of cement-based materials are significantly improved after the addition of appropriate fibers, such as steel fiber (SF) (Al-musawi et al 2019, Roberti et al 2020 , polypropylene (PP) fiber (Marushchak et al 2022, Ma et al 2022, basalt fiber (BF) (Punurai et al 2018, Zheng et al 2019. Some characters (Saje et al 2013, Ma et al 2017, George and Abin Thomas 2020 of fiber, like length, length-diameter ratio and the dosage of fiber, have great influence on the improvement of shrinkage. In the cement hardening stage, these fibers are evenly distributed in matrix and connected with plenty of the pores in the interior, which inhibit partial shrinkage cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers found that the shrinkage properties of cement-based materials are significantly improved after the addition of appropriate fibers, such as steel fiber (SF) (Al-musawi et al 2019, Roberti et al 2020 , polypropylene (PP) fiber (Marushchak et al 2022, Ma et al 2022, basalt fiber (BF) (Punurai et al 2018, Zheng et al 2019. Some characters (Saje et al 2013, Ma et al 2017, George and Abin Thomas 2020 of fiber, like length, length-diameter ratio and the dosage of fiber, have great influence on the improvement of shrinkage. In the cement hardening stage, these fibers are evenly distributed in matrix and connected with plenty of the pores in the interior, which inhibit partial shrinkage cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Expansion of the application areas of fiber-reinforced concrete is possible only if the effectiveness of this implementation is justified, which cannot be done without determining and introducing into the calculation of structural elements improved deformation and strength parameters of fiber-reinforced concrete instead of the traditional characteristics of heavy concrete [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%